2019
DOI: 10.1530/ec-18-0543
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid induces migration through a FFAR1/4, EGFR and AKT-dependent pathway in breast cancer cells

Abstract: Free fatty acids (FFAs) are an energy source, and induce activation of signal transduction pathways that mediate several biological processes. In breast cancer cells, oleic acid (OA) induces proliferation, matrix metalloproteinase-9 (MMP-9) secretion, migration and invasion. However, the signal transduction pathways that mediate migration and invasion induced by OA in breast cancer cells have not been studied in detail. We demonstrate here that FFAR1 and FFAR4 mediate migration induced by OA in MDA-MB-231 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Notably, this was also observed for the highly invasive ACHN cells, which are derived from pleural effusion metastasis. Earlier studies have shown that activating AKT inhibition can suppress cell migration (Marcial-Medina et al, 2019; Mete et al, 2019). Our own results indicated that nobiletin inhibits AKT activation, suggesting that this could be one of the mechanisms underlying the inhibitory effect of nobiletin on the invasion and migration of renal carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this was also observed for the highly invasive ACHN cells, which are derived from pleural effusion metastasis. Earlier studies have shown that activating AKT inhibition can suppress cell migration (Marcial-Medina et al, 2019; Mete et al, 2019). Our own results indicated that nobiletin inhibits AKT activation, suggesting that this could be one of the mechanisms underlying the inhibitory effect of nobiletin on the invasion and migration of renal carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies confirmed the pro-migratory role of AKT2 [151, 157, 164166] and dealt with possible mechanisms behind the crucial role of AKT2 in breast cancer migration, invasion and metastasis. AKT2, but not AKT1 or AKT3, enhances an integrin β1-mediated attachment to and an invasion through collagen IV and to a minor degree through laminin in vitro and in vivo.…”
Section: Akt Isoform Specificity In Breast Cancer: Migration and Invamentioning
confidence: 99%
“…Long-chain (n-6) fatty acids (linoleic acid) are well-known as pro-inflammatory factors, which induce the development of breast cancer [47], whereas other fatty acids reversely impact on the breast cancer patients [43,45,49]. FFAs induce breast cancer invasion by activating the epidermal growth factor receptor, GTP-binding protein, and protein kinase C pathway [57], and by controlling cell proliferation via phosphatidylinositol 3-kinase (PI3K) [58] and cell migration through free fatty acid receptor 1 and 4 and AKT pathway activation [59]. In vitro, David et al stimulated breast cancer cells proliferation by supplement of FFAs on serum-free medium in a dose-dependent manner, linoleic acid can stimulate breast cancer cell growth at three times higher concentration than oleic acid (0.75 µg/mL) [47].…”
Section: Adipocytes Regulate Breast Cancer Via Their Metabolic Submentioning
confidence: 99%